Maneuvering the Peroxidase‐Like Activity of Palladium‐Based Nanozymes by Alloying with Oxophilic Bismuth for Biosensing. Issue 6 (3rd December 2022) - Xia, Shiyu; Wu, Fengxia; Cheng, Lu; Bao, Haibo; Gao, Wenping; Duan, Jin; Niu, Wenxin; Xu, Guobao
Abstract: Engineering the catalytic performance of nanozymes is of vital importance for their broad applications in biological analysis, cancer treatment, and environmental management. Herein, a strategy to boost the peroxidase‐like activity of Pd‐based nanozymes with oxophilic metallic bismuth (Bi) is demonstrated, which is based on the incorporation of oxophilic Bi in the Pd‐based alloy nanocrystals (NCs). To synthesize PdBi alloy NCs, a seed‐mediated method is employed with the assistance of underpotential deposition (UPD) of Bi on Pd. The strong interaction of Bi atoms with Pd surfaces favors the formation of alloy structures with controllable shapes and excellent monodispersity. More importantly, the PdBi NCs show excellent peroxidase‐like activities compared with pristine Pd NCs. The structure–function correlations for the PdBi nanozymes are elucidated, and an indirect colorimetric method based on cascade reactions to determine alkaline phosphatase (ALP) is established. This method has good linear range, low detection limit, excellent selectivity, and anti‐interference. Collectively, this work not only provides new insights for the design of high‐efficiency nanozymes, expands the colorimetric sensing platform based on enzyme cascade reactions, but also represents a new example for UPD‐directed synthesis of alloy NCs. Abstract : Incorporation of oxophilic bismuth by an underpotential deposition strategy endows Pd‐based nanocrystals (NCs) with outstanding nanozyme properties. Mechanistic studies suggest that the oxophilicity of Bi contributes to the excellent peroxidase‐like activity of the alloy NCs, and thus they can be utilized in biosensing with high sensitivity.